2005
DOI: 10.1128/aac.49.5.1943-1948.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Activity of Telithromycin at Simulated Clinically Achievable Free-Drug Concentrations in Serum and Epithelial Lining Fluid against Efflux ( mefE )-Producing Macrolide- Resistant Streptococcus pneumoniae for Which Telithromycin MICs Vary

Abstract: The present study, using an in vitro model, assessed telithromycin pharmacodynamic activity at simulated clinically achievable free-drug concentrations in serum (S) and epithelial lining fluid (ELF) against efflux (mefE)-producing macrolide-resistant Streptococcus pneumoniae. Two macrolide-susceptible (PCR negative for both mefE and ermB) and 11 efflux-producing macrolide-resistant [PCR-positive for mefE and negative for ermB) S. pneumoniae strains with various telithromycin MICs (0.015 to 1 g/ml) were tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
(88 reference statements)
1
24
0
Order By: Relevance
“…One erythromycin-susceptible S. pneumoniae isolate and two erythromycin-resistant S. pneumoniae isolates, including mefA-positive and ermB-positive strains, were tested (16,21,26,27,29,30). The AUC 0-24 /MIC values of S-013420 required for activity against S. pneumoniae were determined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One erythromycin-susceptible S. pneumoniae isolate and two erythromycin-resistant S. pneumoniae isolates, including mefA-positive and ermB-positive strains, were tested (16,21,26,27,29,30). The AUC 0-24 /MIC values of S-013420 required for activity against S. pneumoniae were determined.…”
Section: Resultsmentioning
confidence: 99%
“…This result is supported by characterization of the concentration-dependent bactericidal activity of S-013420 which was indicated by timekill kinetics (12a). As for S. pneumoniae, other studies of macrolide antibiotics also showed that AUC 0-24 /MIC was the dominant parameter which correlated with antibacterial activity and characterized concentration-dependent bactericidal activity (16,21,26,27,29,30). The dominant PK/PD parameter for determination of the efficacy of macrolide antimicrobials was considered to be AUC/MIC, regardless of the bacterial species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For telithromycin, a bactericidal effect was observed when simulated concentrations in serum and epithelial lining allowed to reach a C max /MIC ≥ 3.5 and an area under the curve to MIC ≥ 25 h, but a bacteriostatic effect was observed when these exposures were twice lower. This means that telithromycin at its conventional dosage should be able to eradicate streptococci with an MIC of 0.25 mg L −1 in serum and 1 mg L −1 in epithelial lining fl uid (Zhanel et al 2005 ). This type of approach also led to the conclusion that at human-simulated exposure, telithromycin can achieve higher AUC/MIC ratios than clarithromycin against S. pneumoniae , and therefore higher chances of microbiological eradication, while the contrary holds true for S. aureus (Alferova et al 2005 ).…”
Section: In Vitro Pharmacodynamic Modelsmentioning
confidence: 98%